2019
DOI: 10.5812/asjsm.81771
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Vertical Ground Reaction Force, Sagittal Joint Angles, and the Muscle Co-Contraction Index During Single-Leg Jump-Landing

Abstract: Background: Impact and lower extremity joint angles during landing are factors that can increase the risk of anterior cruciate ligament injuries. However, the correlations between these factors and lower extremity muscle activation during the flight phase, which may affect these factors, are unknown. Objectives: The present study aimed to clarify the correlations between the peak vertical ground reaction force (pVGRF), sagittal joint angles during the landing phase, and the vastus medialis (VM) and semitendino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…A previous study of healthy athletes measured VGRF during single-leg jump landing with the same equipment and method, and the median (interquartile range) pVGRF was 371.7 (83.1) %body weight. 27 Although the results of this study cannot be statistically compared with those of previous studies, the results suggest that the pVGRF of the YRTS group is not larger than that of healthy athletes, but that the pVGRF of the NRTS group is smaller.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A previous study of healthy athletes measured VGRF during single-leg jump landing with the same equipment and method, and the median (interquartile range) pVGRF was 371.7 (83.1) %body weight. 27 Although the results of this study cannot be statistically compared with those of previous studies, the results suggest that the pVGRF of the YRTS group is not larger than that of healthy athletes, but that the pVGRF of the NRTS group is smaller.…”
Section: Discussioncontrasting
confidence: 67%
“…All participants performed a single-leg jump landing task. 27 A 20-cm-high box was placed 60 cm from the centre of the force plate. The participants stood on the step on their measurement leg with the opposite hip and knee bent at 45° and 90°, respectively, and neutral hip rotation.…”
Section: Methodsmentioning
confidence: 99%
“…This supports previous findings which concluded that volleyball players seem to be able to absorb an impact force between 1.9 to 4.0 times their body weight [ 31 , 39 , 40 ]. These results might be related to lower limb movement, wherein a negative correlation between knee flexion and the magnitude of the peak GRF is found [ 41 , 42 ]. This could be also due to the nature of volleyball wherein, rather than gymnastics during landing, volleyball players must control their GRF quickly in order to react to any other unexpected stimuli incoming from the game [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study comparing the biomechanics of double‐ and single‐leg landing tasks showed that the double‐leg landing task may not adequately represent the risk of ACL injury 31 . Thus single‐leg jump landing was assessed based on a previous study 32 . Participants performed a single‐leg jump landing task with their operated leg.…”
Section: Methodsmentioning
confidence: 99%
“…31 Thus single-leg jump landing was assessed based on a previous study. 32 Participants performed a single-leg jump landing task with their operated leg. A 20-cm-high box was placed 60 cm from the center of force plate.…”
Section: Self-reported Questionnairesmentioning
confidence: 99%